Facile design of ultra-thin anodic aluminum oxide membranes for the fabrication of plasmonic nanoarrays. (31st January 2017) - Hao, Qi; Huang, Hao; Fan, Xingce; Hou, Xiangyu; Yin, Yin; Li, Wan; Si, Lifang; Nan, Haiyan; Wang, Huaiyu; Mei, Yongfeng; Qiu, Teng; Chu, Paul K
Abstract: Ultra-thin anodic aluminum oxide (AAO) membranes are efficient templates for the fabrication of patterned nanostructures. Herein, a three-step etching method to control the morphology of AAO is described. The morphological evolution of the AAO during phosphoric acid etching is systematically investigated and a nonlinear growth mechanism during unsteady-state anodization is revealed. The thickness of the AAO can be quantitatively controlled from ∼100 nm to several micrometers while maintaining the tunablity of the pore diameter. The AAO membranes are robust and readily transferable to different types of substrates to prepare patterned plasmonic nanoarrays such as nanoislands, nanoclusters, ultra-small nanodots, and core–satellite superstructures. The localized surface plasmon resonance from these nanostructures can be easily tuned by adjusting the morphology of the AAO template. The custom AAO template provides a platform for the fabrication of low-cost and large-scale functional nanoarrays suitable for fundamental studies as well as applications including biochemical sensing, imaging, photocatalysis, and photovoltaics.